ALAT PERMAINAN EDUKATIF FLASHCARD ALFABET SEBAGAI MEDIA PEMBELAJARAN UNTUK ANAK USIA DINI - Dzulkifli Dzulkifli; andini dwi arumsari; Ummi Masrufah Maulidiyah (Universitas Narotama, 2022)
FLASHCARD ALFABET is a learning medium in the form of an educational game tool (APE) that aims to help early childhood in learning to memorize letters A-Z, compose words and also be able to know colors. The game is designed to train fine motor skills in preschool students. This research uses a Descriptive type with a Qualitative approach, the data collection technique in this study is by observation and interview methods. This research was conducted at HANGTUAH 9 Kindergarten located on Jl.Mess Ampel Ujung, Semampir District, Surabaya City. The subjects in this study were all students of TK A Hangtuah 9 class aged 5 years. The results of the study, namely after the researchers conducted experiments for 3 consecutive times in 2 days during school class hours, with the same time on the first and second days using the ALPHABET FLASHCARD that the researcher made and obtained the results showed that the subjects experienced an improvement in the ability to memorize the letters A-Z, distinguish colors, Compose words, and the subject's fine k motori also improved. Keywords: Educational Game Tools, Ability to memorize letters A-Z, ability to Compose words, ability to distinguish colors, fine motor.